2015
DOI: 10.1242/dev.115147
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome regulation of the chromodomain protein MRG-1 controls the balance between proliferative fate and differentiation in theC. elegansgerm line

Abstract: The level of stem cell proliferation must be tightly controlled for proper development and tissue homeostasis. Multiple levels of gene regulation are often employed to regulate stem cell proliferation to ensure that the amount of proliferation is aligned with the needs of the tissue. Here we focus on proteasome-mediated protein degradation as a means of regulating the activities of proteins involved in controlling the stem cell proliferative fate in the C. elegans germ line. We identify five potential E3 ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…We quantified the accumulation of three well‐known interaction partners, i.e , two chromatin regulatory proteins, MORF 4L1 and L2, and MRFAP1, in both cell lines after proteasome inhibition (Supporting Information figure S6B). Recent studies have shown that MRFAP1 proteins have fast turnover rates, and are rapidly degraded via the ubiquitin‐proteasome system . This protein and its interaction partner MORF4L1 were found amongst the most up‐regulated proteins after NEDD8 inhibition, in multiple human cell lines .…”
Section: Resultsmentioning
confidence: 98%
“…We quantified the accumulation of three well‐known interaction partners, i.e , two chromatin regulatory proteins, MORF 4L1 and L2, and MRFAP1, in both cell lines after proteasome inhibition (Supporting Information figure S6B). Recent studies have shown that MRFAP1 proteins have fast turnover rates, and are rapidly degraded via the ubiquitin‐proteasome system . This protein and its interaction partner MORF4L1 were found amongst the most up‐regulated proteins after NEDD8 inhibition, in multiple human cell lines .…”
Section: Resultsmentioning
confidence: 98%
“…Post-translational mechanisms including ubiquitin-mediated proteolysis have been implicated in the control of germline stem cell differentiation (Macdonald et al 2008;Jeong et al 2011;Gupta et al 2015). GLD-1 expression is qualitatively recapitulated by translational reporters (Merritt et al 2008), and our quantitative analysis of reporter GFP accumulation suggests that most of the quantitative control of GLD-1 levels in the distal germline is mediated through regulation of the gld-1 39 UTR ( Figure S4), indicating that post-translation control of GLD-1 accumulation plays only a minor role in regulating GLD-1 levels in the proliferative zone.…”
Section: Gld-1 Activation Region (mentioning
confidence: 99%
“…However, the use of DAPI staining in this study did not allow detection of PZ cells remaining at hours 6-8 (Figure 4) because chromosome morphology does not allow an unambiguous classification of individual germ-cell fate [see also Figure S2 in which we analyze glp-1(q224)]. In contrast, the use of REC-8/HIM-3 costaining can distinguish between PZ cells and meiotic prophase cells, even when they are intermixed, as often occurs in the meiotic entry region in wild type and in certain incompletely penetrant germline tumor mutants (MacQueen and Villeneuve 2001;Hansen et al 2004a;Fox et al 2011;Gupta et al 2015). To illustrate the distinction between antibody markers and DAPI morphology, Figure 2A (arrowhead) shows a cell that has entered meiosis (HIM-3 positive; REC-8 negative) whose nucleus shows sphericalrather than crescent-shaped DAPI morphology.…”
Section: Cells Throughout the Proliferative Zone Rapidly And Synchronmentioning
confidence: 99%